2020
DOI: 10.1080/03075079.2019.1711041
|View full text |Cite
|
Sign up to set email alerts
|

Permanent contracts and job satisfaction in academia: evidence from European countries

Abstract: Temporary contracts are increasingly used in academia. This is a major concern for non-tenured researchers, since weak job security may hamper job satisfaction. This paper presents an empirical analysis of the role of academic tenure for job satisfaction of researchers in European countries. The work uses data from the MORE2 survey, a large-scale representative survey of researchers in all European countries. The results show that, ceteris paribus, academics with a permanent contract are on average more satisf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 34 publications
4
37
0
1
Order By: Relevance
“…The legacy of danwei system ensures these academics lifetime job security while they are subject to performance-based evaluation. This supports Castellacci and Viñas-Bardolet's (2020) argument that academics with a permanent contract tend to experience less job insecurity than those employed with casualization. On the other hand, CE teachers demonstrated little resistance.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The legacy of danwei system ensures these academics lifetime job security while they are subject to performance-based evaluation. This supports Castellacci and Viñas-Bardolet's (2020) argument that academics with a permanent contract tend to experience less job insecurity than those employed with casualization. On the other hand, CE teachers demonstrated little resistance.…”
Section: Discussionsupporting
confidence: 82%
“…The specificity of the Chinese context renders CE teachers some uniqueness. Unlike many of their western counterparts employed by temporary forms of contract (e.g., Castellacci & Viñas-Bardolet, 2020;Strauss, 2020), CE teachers seldom reported job insecurity in terms of being laid off. CE teachers in our case were all recruited before or at the time when HE institutions in China started the transition from the danwei system, the "paternalistic management" model by the Chinese government (Huang et al, 2016, p. 4) to the new personnel system based on contract-based employment and performance-related pay.…”
Section: Discussionmentioning
confidence: 84%
“…While as noted by Mitchell (2011), there are a meager number of published empirical investigations carried out focusing on the job satisfaction of employees within the framework of AET, our review shows that still this area has been relatively unexplored in the higher education research domain (e.g., Castellacci and Viñas-Bardolet (2020), Schlesinger et al (2017), Kuwaiti et al (2019), andTayfur Ekmekci et al (2018)). In addition to that, the examination of the impact of employee affective reactions on workplace situations, as an important and promising area of social research (Tillman et al, 2018), provided additional motivation for this study.…”
Section: Introductionmentioning
confidence: 71%
“…Job-related controls include one variable that takes the value of one for those who hold a permanent job position. Recent research has shown that temporary contracts hamper job satisfaction both among workers in the academic sector (Waaijer et al , 2017; Castellacci and Viñas-Bardolet, 2020) and outside it (Chadi and Hetschko, 2016). Besides this covariate, we also considered two variables that measure the link between respondents' post-PhD activities and R&D. We assume that the stronger this link is, the higher the doctoral graduates' satisfaction.…”
Section: Methodsmentioning
confidence: 99%